Prestasi Belajar Bahasa Inggris pada Siswa SMA pada Pelaksanaan Sistem Pembelajaran Kurikulum 2013 - Nursaly, Baiq Rismarini; Nazri, M. Adib; Handini, Baiq Suprapti; Murcahyanto, Hary (JOEAI (Journal of Education and Instruction), 2021)
This study aims to describe the effect of implementing the 2013 curriculum learning system on high school students' English learning scores, and how much influence the 2013 curriculum learning system implementation has on high school students' English subject scores. This research is quantitative descriptive. The population in this study were all students of class XI IPS SMA Negeri 1 Selong, with a total population of 63 students, a sample of 54 students, with an error threshold of 5%. The variables in this study are; (1) the implementation of the 2013 curriculum learning system (X), and (2) the academic achievement variable (Y). The data collection technique used the recording method, the questionnaire survey method, the observation method and the interview method. Using the SPSS program calculation tool for Windows version 16, using linear regression analysis techniques to analyze the collected data. The results of this study indicate that the application of the 2013 course learning system has no effect on the achievement of social studies students in class XI SMA Negeri 1 Selong, the effective contribution of the implementation of the curriculum learning system on the achievement of learning English in class XI social studies is 0.001%, and the coefficient of determination is 0.001%. Based on the results of the study, it can be concluded that the implementation of the 2013 curriculum learning system has no effect on the academic achievement of the XI IPS class students of SMA Negeri 1 Selong in English lessons in 2019. Keywords: 2013 Curriculum, Learning Achievement, Learning System